Kesiapsiagaan Masyarakat dalam Menghadapi Potensi Bencana Kawasan Pesisir di Pantai Tambakrejo Kabupaten Blitar - Ella Putri Permatasari; Hendra Pratama (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Disasters are events that can cause loss of life, environmental damage, property loss, and psychological impacts on communities. Disaster preparedness is a crucial aspect in reducing risks and minimizing impacts through appropriate and effective measures. Tambakrejo Beach in Blitar Regency is prone to disasters such as earthquakes, tsunamis, and tidal floods due to its physical characteristics as a shallow bay directly adjacent to the Indian Ocean. This study aims to analyze the physical conditions and disaster history, the role of the government in disaster mitigation, and the level of community preparedness in the coastal area of Tambakrejo Beach. This research employs a quantitative approach with a descriptive method. Data were collected through observation, questionnaires, interviews, and documentation, with respondents selected using purposive sampling techniques. The results indicate that Tambakrejo Beach has a high level of vulnerability to both tsunamis and tidal floods. The government's role in mitigating tidal floods remains largely reactive and is not yet supported by adequate early warning systems. In contrast, tsunami mitigation efforts are more developed through Disaster Resilient Village programs, training, and community outreach. Community preparedness is generally adequate in terms of knowledge; however, it remains limited in technical understanding, emergency response planning, and resource mobilization, particularly for tidal flood hazards. Therefore, strengthening early warning systems, enhancing education, and improving community capacity are essential to achieving comprehensive disaster preparedness.